Species Inventory of Brittel Stars (Ophiuroidea) at Bilik Beach, Baluran National Park, East Java - Rendy Setiawan; Fresha Aflahul Ula; Santi Feronika Sijabat (Jurnal Perikanan dan Kelautan, 2018)
The Brittle stars is a member of the Phylum Echinodermata that lives in habitats in the intertidal, subtidal, and deep sea zones. Brittle stars can be found in areas of coral reefs, sand, seagrass, macroalgae (seaweed), and dead coral fragments. One of the many intertidal areas of the brittle stars habitat is in the Bilik Beach, Baluran National Park. Ophiuroidea is important to be studied in the conservation area, Baluran National Park, because it is a natural conservation area that has native ecosystems and is managed with a zonation system and utilized for natural tourism, research, science and education purposes. This study aims to determine the type of brittle stars found on the Baluran National Park. The method used in this research is descriptive method with road sampling technique in the Bilik Beach area. The brittle stars species found and described are 8 species, namely Ophiomastix annulosa, Ophiocoma scolopendrina, O. brevipes, Ophioplocus imbricatus, Ophiolepis cardioplax, O. superba, Ophiarachna parvispina, and Macrophiothrix longipeda.